DASAMUKA PEJAH SEBAGAI IDE PENCIPTAAN KARYA SENI LUKIS - Junaedi, Yuda; Cahyana, Agus; Sujana, Anis (ATRAT: Jurnal Seni Rupa, 2024)
This study highlights the importance of examining the tragic and romantic expressions of Dasamuka, the antagonist character in Ramayana paintings, as a reflection of Indonesian culture from a contemporary perspective. These artworks serve as a means to understand the complexity of human nature within the context of Indonesia’s rich historical and cultural heritage. The research employs an indirect method with specific stages, including material selection, visual sketches of Dasamuka, choosing object interactions, and selecting narrative backdrops with glimpses of tragic stage elements, expressive movements, lighting techniques, and finishing touches. The result is a painting that portrays the tragic and romantic expressions of Dasamuka, honing the artist’s ability to create unique and expressive works while preserving Indonesian cultural values. By placing the antagonist character at the center of discussion, this Ramayana painting offers a new dimension to the classic tale and invites the audience to realize that each character has their own story and reasons. Through this artwork, Indonesian society, especially the younger generation, is reminded of the importance of preserving cultural identity and local wisdom values. Moreover, this artwork serves as a means to strengthen and preserve Indonesia’s cultural identity amidst the rapid waves of globalization.